Changes and continuities in a Mediterranean landscape: a new interdisciplinary approach to understanding historic character in western Catalonia. (3rd October 2018) - Turner, Sam; Bolòs, Jordi; Kinnaird, Tim
Abstract: To understand why historic landscapes changed in the past researchers need to identify when and where changes took place, but in rural landscapes, the origins and development of many historic elements including field systems, roads, terraces and other earthworks remain poorly understood. This paper outlines a practical interdisciplinary method using GIS-based historic landscape characterisation (HLC) to integrate data from different sources and model how historic character varies in space. It pilots an innovative approach using luminescence profiling and dating that can underpin the HLC with significantly improved knowledge of historic processes of change. We focus on four case studies of terraced agricultural landscapes in western Catalonia and demonstrate for the first time that existing terrace systems often have medieval or early modern origins.